PELAKSANAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMK NEGERI 1 LAIS KECAMATAN LAIS KABUPATEN MUSI BANYUASIN - Suyadi Suyadi (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2014)
Abstract: The problem for school children usually do not like the lessons he considered difficult. This issue will certainly affect the ability of understanding the concept of learning itself. Therefore must be considered principles of good teaching so that learning is always a problem for students can be overcome. The principles include: 1) the need to prepare children for learning, 2) starting from the concrete to the abstract, 3) providing opportunities for children to practice and repeat, 4) generalize to new situations, 5) departed from the strengths and weaknesses students, 6) the need to build a strong foundation in the concepts and skills, 7) the provision of a balanced program, and 8) the use of media (Amilda 2010, p. 159).It should be understood by the teacher when the learning process, the teacher in the classroom not only provide knowledge or values of the teacher as a storehouse of knowledge and students are like empty bottles are filled, but should be able to provide stimulus and intelligently implemented in the classroom, but students should be able to be made to think eduktif and can build a good human types and plenary (complete and incomplete) (Kartono, 2001, p. 10).The teacher is the holder of a leading role in the implementation of learning. The process of learning is a process that contains a series of acts or teachers and learners basic reciprocal relationships that take place in an educational situation to achieve a certain goal. In simple terms, the teacher is the one who gives knowledge to the students (Djamarah, 2005, p. 31). Keywords: Teacher competent, effective, and responsibilities of shareholders leading role in the implementation of learning.